Evaluation of regional project to strengthen national health research systems in four countries in West Africa: lessons learned - Issiaka Sombié; Jude Aidam; Gabriela Montorzi (BMC, 2017)
Abstract Background Since the Commission on Health Research for Development (COHRED) published its flagship report, more attention has been focused on strengthening national health research systems (NHRS). This paper evaluates the contribution of a regional project that used a participatory approach to strengthen NHRS in four post-conflict West African countries - Guinea-Bissau, Liberia, Sierra Leone and Mali. Methods The data from the situation analysis conducted at the start of the project was compared to data from the project's final evaluation, using a hybrid conceptual framework built around four key areas identified through the analysis of existing frameworks. The four areas are governance and management, capacities, funding, and dissemination/use of research findings. Results The project helped improve the countries' governance and management mechanisms without strengthening the entire NHRS. In the four countries, at least one policy, plan or research agenda was developed. One country put in place a national health research ethics committee, while all four countries could adopt a research information management system. The participatory approach and support from the West African Health Organisation and COHRED were all determining factors. Conclusion The lessons learned from this project show that the fragile context of these countries requires long-term engagement and that support from a regional institution is needed to address existing challenges and successfully strengthen the entire NHRS.